Systematic Literature Review: The Role Of ICAO Standard Phraseology In The Prevention Of Aircraft Accidents And Incidents - Citra Puspitaningrum; Elfi Amir; Rany Adiliawijaya Putriekapuja (International Journal of Health Engineering and Technology, 2026)
Aviation safety is significantly influenced by the effectiveness of communication between pilots and Air Traffic Controllers (ATC). One effort to minimize communication errors is the implementation of ICAO Standard Phraseology as an international communication standard in aviation operations. This study aims to analyze the role of ICAO Standard Phraseology in preventing aircraft accidents and incidents through a Systematic Literature Review (SLR) approach. The review process was conducted using the PRISMA method, including the identification, screening, evaluation, and synthesis of literature obtained from various academic databases. The results of the review of nine articles indicate that ICAO Standard Phraseology contributes to reducing communication ambiguity, suppressing human error, increasing situational awareness, and supporting more informed decision-making between pilots and ATC. However, the effectiveness of its implementation is still influenced by Aviation English skills, personnel experience, and adherence to communication procedures. Therefore, aviation communication training and evaluation need to be continuously improved to optimally support aviation safety.